How Do Women Interpret the NHS Information Leaflet about Cervical Cancer Screening?. (October 2019) - Okan, Yasmina; Petrova, Dafina; Smith, Samuel G.; Lesic, Vedran; Bruine de Bruin, Wändi
Background. Organized screening programs often rely on written materials to inform the public. In the United Kingdom, women invited for cervical cancer screening receive a leaflet from the National Health Service (NHS) to support screening decisions. However, information about screening may be too complex for people to understand, potentially hindering informed decision making.Objectives. We aimed to identify women's difficulties in interpreting the leaflet used in England and negative and positive responses to the leaflet.Methods. We used a sequential mixed-methods design involving 2 steps: cognitive think-aloud interviews ( n = 20), followed by an England-wide survey ( n = 602). Data were collected between June 2017 and December 2018, and participants included women aged 25 to 64 y with varying sociodemographics.Results. Interview results revealed misunderstandings concerning screening results, benefits, and additional tests and treatment, although participants tended to react positively to numerical information. Participants were often unfamiliar with the potential harms associated with screening (i.e., screening risks), key aspects of human papillomavirus, and complex terms (e.g., dyskaryosis ). Survey results indicated that interpretation difficulties were common ( M correct items = 12.5 of 23). Lower understanding was associated with lower educational level (β's >0.15, P 's <0.001), lower numeracy scores (β = 0.36, P < 0.001), and nonwhite ethnicity (β = 0.10, P = 0.007). The leaflet was evaluated positively overall.Conclusions. Despite previous user testing of the leaflet, key information may be too complex for some recipients. As a consequence, they may struggle to make informed decisions about screening participation based on the information provided. We discuss implications for the improvement of communications about screening and decision support.